2022
DOI: 10.21037/qims-21-189
|View full text |Cite
|
Sign up to set email alerts
|

Identification of histological features of endometrioid adenocarcinoma based on amide proton transfer-weighted imaging and multimodel diffusion-weighted imaging

Abstract: Background: Noninvasive identification of the histological features of endometrioid adenocarcinoma is necessary. This study aimed to investigate whether amide proton transfer-weighted imaging (APTWI) and multimodel (monoexponential, biexponential, and stretched exponential) diffusion-weighted imaging (DWI) could predict the histological grade of endometrial adenocarcinoma (EA). In addition, we analyzed the correlation between each parameter and the Ki-67 index.Methods: A total of 90 EA patients who received pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…The stretched exponential model IVIM generates α, a parameter reflecting the complexity of the tissue. Previous studies have found that due to the higher level of intravoxel microscopic necrotic foci, heterogeneous cellularity, and heterogeneous cellularity, the tissue complexity of highproliferation lesions tends to be higher than that of lowproliferation lesions, and therefore α tends to decrease in high-proliferation lesions (38,39). These results are consistent with those of the present study, suggesting that α can play an important role in the assessment of EC proliferation.…”
Section: Evaluation Of Ivim For Ecsupporting
confidence: 92%
“…The stretched exponential model IVIM generates α, a parameter reflecting the complexity of the tissue. Previous studies have found that due to the higher level of intravoxel microscopic necrotic foci, heterogeneous cellularity, and heterogeneous cellularity, the tissue complexity of highproliferation lesions tends to be higher than that of lowproliferation lesions, and therefore α tends to decrease in high-proliferation lesions (38,39). These results are consistent with those of the present study, suggesting that α can play an important role in the assessment of EC proliferation.…”
Section: Evaluation Of Ivim For Ecsupporting
confidence: 92%
“…13 Previous publications have demonstrated that D* values with poor stability and repeatability could not effectively evaluate histopathological information of earlystage EC due to the influence of the scanning parameters, the ROI determination method, the signal-to-noise ratio (SNR), and other factors. [17][18][19][20] In this study, there was no statistically significant difference in D* between the TP53-mutant and TP53wild groups, and the low-risk and the non-low-risk groups, which was consistent with the above research, further proving that the D* value was unable to play a role in the assessment of TP53 status and risk stratification in early-stage EC.…”
Section: Prediction Of Tp53 Status and Risk Stratification Of Early-s...supporting
confidence: 86%
“…17,19 The reason may be that there were differences in histological grade, FIGO stage, and lymph node metastasis between the low-risk and non-low-risk early-stage EC, resulting in different degrees of influence on the diffusion of water molecules and ultimately leading to significant differences in D values between the two groups. 18,20 D* was a perfusion parameter of IVIM that is mainly correlated with the velocity of blood flow within the microcirculation. 13 Previous publications have demonstrated that D* values with poor stability and repeatability could not effectively evaluate histopathological information of earlystage EC due to the influence of the scanning parameters, the ROI determination method, the signal-to-noise ratio (SNR), and other factors.…”
Section: Prediction Of Tp53 Status and Risk Stratification Of Early-s...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the size of the f value is not only related to the microvessel density and blood flow velocity but also to the overall motion of the water molecules in the tissue, the pressure of the blood vessel wall, and the difference in the b-value. [35][36][37][38] Previous reports 39,40 have shown that the choice of b value varies, and the size of f value also varies. For instance, an IVIM study 39 on prostate cancer showed that when the b values were within a range of 0-750 sec/mm 2 , the f value of the tumor tissue increases, but when the maximum b value exceeds 750 sec/mm 2 , the f value of the tumor tissue decreases significantly, making it indistinguishable from normal tissue.…”
Section: Discussionmentioning
confidence: 99%